Factors Affecting the Utilisation of Time as a Selected Teaching/Learning Resource in Public Day Secondary Schools in Nyacheki Division, Kisii County, Kenya - Omae, David. O.; Onderi, Peter Omae; Mokogi, Henry Marita; Bantu, Edward; Barongo, Samson; Miroro, Risper.S.; Evans, Mokaya N. (American Journal of Education and Learning, 2016)
The Kenyan government provides financial and technical help for the provision of teaching learning resources in secondary schools Despite the government’s effort to allocate resources to secondary schools, there is still underutilization of these resources. The purpose of this study was to establish factors affecting utilization of time as a selected resource in public day secondary schools in Nyacheki Division, Nyamache District, Kisii county of Kenya. The study adopted a descriptive survey research design. The target population was all teachers and students in public day secondary schools in Nyacheki Division. Purposive sampling was used to select respondents who comprised of 87 Heads of departments. Krejcie and Morgan’s formula was used to obtain the sample of 341 students from 20 selected schools. Two questionnaires were used for data collection; the teachers’ questionnaire and the students’ questionnaire. The research instruments were pilot tested in two randomly selected public day secondary schools. The reliability coefficients of the instruments of this study were estimated using Cronbach’s Alpha Coefficient as 0.89 and 0.83 for teachers and students questionnaires respectively. Data was analyzed using descriptive statistics. The findings of the study indicate that poor institutional policies, management skills and planning lead to ineffective utilization of time. Further, the poor attitude of the teachers and students play a key role in the ineffective utilization of this resource. The study has recommended that, there should be continuous skills upgrading for teachers, disciplined team spirit, and creation of a healthy working environment.